(untitled) (Journal of Health, Technology and Science (JHTS), 2025)
Cattle are animals that are raised by many people compared to other livestock. Cows can produce various benefits such as as as a source of milk, as a working animal in rice fields, and meat producers and for the fulfillment of food needs, especially animal protein, beef in addition to having high nutritional value beef is also a medium for the growth of diseases, one of which is Taeniasis caused by the worm parasite Taenia saginata. The purpose of this study was to identify Taenia saginata tapeworm in beef sold at the Traditional Market (Thursday-Friday) of Bone Bolango Regency. The type of research used is a qualitative approach with observational sample collection techniques. The type of data used is primary data in the form of research results and secondary data in the form of data from literature, parasite atlases, and previous penelit I data. This study uses descriptive data analysis techniques, namely describing the morphological characteristics of the Taenia saginata worm based on microscopic observations. The results obtained during this study were that out of 10 beef samples that were used as the object of study, Taenia saginata worms were found positive in 4 samples while 6 other samples were found positive for Oesophagustomum sp and Cooperia sp worms.